2021
DOI: 10.1021/acs.est.1c01773
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Verification of Barrierless HONO Formation from the Oxidation Reaction System of NO, Cl, and Water in the Atmosphere

Abstract: Nitrous acid (HONO) is a major source of hydroxyl (OH) radicals, and identifying its source is crucial to atmospheric chemistry. Here, a new formation route of HONO from the reaction of NO with Cl radicals with the aid of one or two water molecules [(Cl) (NO) (H 2 O) n (n = 1−2)] as well as on the droplet surface was found by Born−Oppenheimer molecular dynamic simulation and metadynamic simulation. The (Cl) (NO) (H 2 O) 1 (monohydrate) system exhibited a free-energy barrier of approximately 0.95 kcal mol −1 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Another ab initio MD method, known as Born–Oppenheimer molecular dynamics (BOMD), includes electronic structure calculations in MD simulations by reducing the electronic structure component by solving the time-independent Schrodinger equation (i.e., QM), while classical MD treats fixed nuclear positions. BOMD simulations determined the heterogeneous reaction for nitrous acid formation from nitric oxide, •Cl radicals, and water on a droplet surface . It was found that the formation of nitrous acid for a dihydrate vs a monohydrate system is energetically more favorable, as evidenced by the absence of a free-energy barrier.…”
Section: Computational Chemistry Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another ab initio MD method, known as Born–Oppenheimer molecular dynamics (BOMD), includes electronic structure calculations in MD simulations by reducing the electronic structure component by solving the time-independent Schrodinger equation (i.e., QM), while classical MD treats fixed nuclear positions. BOMD simulations determined the heterogeneous reaction for nitrous acid formation from nitric oxide, •Cl radicals, and water on a droplet surface . It was found that the formation of nitrous acid for a dihydrate vs a monohydrate system is energetically more favorable, as evidenced by the absence of a free-energy barrier.…”
Section: Computational Chemistry Methodsmentioning
confidence: 99%
“…BOMD simulations determined the heterogeneous reaction for nitrous acid formation from nitric oxide, •Cl radicals, and water on a droplet surface. 299 It was found that the formation of nitrous acid for a dihydrate vs a monohydrate system is energetically more favorable, as evidenced by the absence of a free-energy barrier. The reaction was studied on the surface of a water droplet by BODM and showed that bond breaking in nitric oxide and •Cl radicals occurs only in water molecules for both monohydrate and dihydrate systems.…”
Section: Acs Esandt Engineeringmentioning
confidence: 99%
“…Heterogeneous transformations of chemical pollutants were conventionally investigated using molecular dynamics methods, such as ab initio molecular dynamics (AIMD) and hybrid quantum-mechanical/molecular-mechanical molecular dynamics simulations. These methods were limited to reactions with low energy barriers (typically <2 kcal·mol –1 ), as reactions with higher energy barriers require an extremely long time to reach transition states …”
Section: Potential Applications In Environmental Chemistrymentioning
confidence: 99%
“…Both laboratory and field studies found that photolysis of adsorbed HNO 3 and particulate nitrate (NO − 3 ) could produce HONO (Ye et al, 2016(Ye et al, , 2017Zhou et al, 2003Zhou et al, , 2002bZhou et al, , 2011, which might be an important HONO source, at least in remote areas and polar regions. Evidence of other new pathways and mechanisms has also been found and their atmospheric relevance discussed (Ge et al, 2019;Wang et al, 2016;Xu et al, 2019;Xia et al, 2021;Zhao et al, 2021;Gen et al, 2021).…”
Section: Introductionmentioning
confidence: 95%